Design of Pin On Disc Tribometer Test Equipment Using the Hatamura Method - Dedi Rosa Putra Cupu; Oktaviandi Adeka Putra (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
To determine the rate of wear and coefficient of friction, a test instrument is used, namely a tribometer with a pin on disc type. Before manufacturing, it is necessary to have a design that must comply with existing standards. This study aims to design a pin on disc tribometer with circular motion and reciprocating linear motion using the Hatamura method and its main components, analyze the shaft and frame and produce working papers in the form of technical drawings and bill of materials in the manufacture of test equipment. Pin-on-disc tribometer. In this study, designing several concepts of the pin on disc Tribometer according to the Hatamura method and then evaluating the existing concepts and selecting concepts based on the decision matrix, then the concepts will be designed and analyzed by manual calculations and validation using Autodesk Inventor to determine stress, deflection, as well as safety factors on the axle and frame. The final result of this research is a technical document in the form of layout drawings and assembly drawings as well as detailed drawings of each component and bill of materials.